Multi-Criteria Decision Analysis for healthcare decisions: a bibliometric study - Smirna Marques Felinto da Silveira Fernandes; Renan Felinto de Farias Aires (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2024)
Healthcare has a direct impact on human life and involves risk factors, uncertainties and preferences. The complexity and implications of actions in this area and the demand for rational and transparent decision processes has resulted in the widespread use of Multi-Criteria Decision Analysis (MCDA) methods. As such, this study aimed to conduct a bibliometric analysis of the literature on the use of MCDA in healthcare, as well as analyzing the reasons presented in the articles for selecting MCDA methods, when applicable. The study analyzed 195 articles in the Scopus and PubMed databases between 1991 and 2019. The results were presented in graphs that focused on the main objectives of the study, highlighting the fact that only 28% of the articles presented justifications for the methods chosen. Many of the justifications were not well founded. It was concluded that care is needed to ensure appropriate selection of multi-criteria methods.